Solubility of Ibuprofen with Poloxamer 407 and L-leucine in water and ethanol co-solvent - Hossain, Rubaiya (Brac University, 2020)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Pharmacy, 2019.